γ-Fe2O3@Polyaniline-Chlorambucil Synthesized by Using Doping/Dedoping Method of Polyaniline - Shen, Qian; Lang, Jianping; Kan, Jinqing (Asian Journal of Chemistry, 2014)
The g-Fe2O3@polyaniline-chlorambucil composite has been synthesized. The g-Fe2O3@PANI is modified by chlorambucil (CHB, a chemotherapeutic drug) based on the unique doping-dedoping mechanism of the polyaniline, which don't change doped groups of the chlorambucil. It is confirmed by XRD, VSM, FT-IR and TEM that the chlorambucil was doped into g-Fe2O3@PANI. The experimental results showed that the g-Fe2O3@PANI-CHB has the superparamagnet, electrochemical activity and good conductivity. The poly(vinyl, pyrrolidone) surfactant could improve the suspensibility of g-Fe2O3@PANI-CHB in the aqueous solution. The g-Fe2O3@PANI-CHB could be concentrated in a magnetic field. The concentration of the g-Fe2O3@PANI-CHB at 3000 Gauss was 6 times higher than that of the original solution at a flow rate of 0.1118 g s-1. The results showed that g-Fe2O3@PANI-CHB can kill Madin Darby Canine Kidney (MDCK) but there is no toxic effect of g-Fe2O3@PANI on Madin Darby Canine Kidney cells.